2009
DOI: 10.1088/0953-4075/42/17/175503
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian modelling and Schmidt modes of SPDC biphoton states

Abstract: A double-Gaussian model and the Schmidt modes are found for the biphoton wave function characterizing spontaneous parametric down-conversion with the degenerate collinear phase-matching of the type I and with a pulsed pump. The obtained results are valid for all durations of the pump pulses, short, long and intermediately long.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 8 publications
0
56
0
Order By: Relevance
“…It has been shown that the Schmidt modes for the SPDC biphoton state are given by the Hermite Gaussian polynomials [26,27]. Therefore they show a certain symmetry:…”
Section: Interferometric Scheme and Measurementmentioning
confidence: 99%
“…It has been shown that the Schmidt modes for the SPDC biphoton state are given by the Hermite Gaussian polynomials [26,27]. Therefore they show a certain symmetry:…”
Section: Interferometric Scheme and Measurementmentioning
confidence: 99%
“…We will analyze the entanglement by performing Schmidt decomposition of the two-photon state, which is known as a useful approach to characterize bi-partite pure-state entanglement [45][46][47]. Such an approach has been applied to various atomic and optical systems [48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…the whole dimensionality of the biphoton in the two-dimensional transverse space supposed isotropic. For an unidimensional system, V becomes the square of the Schmidt number 23 .…”
mentioning
confidence: 99%